Penerapan Content Marketing Melalui Social Media Tiktok Pada UMKM MAECHA.ID - Ananda, Reyvanza Adliva; Husrizalsyah, Dedy (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to determine the impact of content marketing on brand awareness and sales improvement, as well as to implement content marketing for UMKM Maecha.id on the TikTok platform. The study employs a quantitative method by collecting data through questionnaires distributed to Maecha.id consumers who have interacted with Maecha.id's TikTok content. The data analysis technique used is simple linear regression. The results of the study indicate that the Content Marketing variable (X) implemented through TikTok has a positive and significant impact on the Brand Awareness variable (Y1), with a t-value of 12.992 and a significance level of 0.000 (< 0.05). The Content Marketing variable (X) implemented through TikTok also positively and significantly affects the Sales Improvement variable (Y2), with a t-value of 9.443 and a significance level of 0.000 (< 0.05). These findings demonstrate that Content Marketing has a significant positive influence on enhancing Brand Awareness and Sales Improvement for UMKM Maecha.id. They also highlight the importance of marketing strategies in the form of content marketing with video content specifically designed for TikTok audiences as an effort to expand market reach and improve Maecha.id's competitiveness.